The MolSSI QCArchive project: An open‐source platform to compute, organize, and share quantum chemistry data. (31st July 2020) - Smith, Daniel G. A.; Altarawy, Doaa; Burns, Lori A.; Welborn, Matthew; Naden, Levi N.; Ward, Logan; Ellis, Sam; Pritchard, Benjamin P.; Crawford, T. Daniel
Abstract: The Molecular Sciences Software Institute's (MolSSI) Quantum Chemistry Archive (QCArchive ) project is an umbrella name that covers both a central server hosted by MolSSI for community data and the Python‐based software infrastructure that powers automated computation and storage of quantum chemistry (QC) results. The MolSSI‐hosted central server provides the computational molecular sciences community a location to freely access tens of millions of QC computations for machine learning, methodology assessment, force‐field fitting, and more through a Python interface. Facile, user‐friendly mining of the centrally archived quantum chemical data also can be achieved through web applications found at https://qcarchive.molssi.org . The software infrastructure can be used as a standalone platform to compute, structure, and distribute hundreds of millions of QC computations for individuals or groups of researchers at any scale. The QCArchive Infrastructure is open‐source (BSD‐3C), code repositories can be found at https://github.com/MolSSI, and releases can be downloaded via PyPI and Conda. This article is categorized under: Electronic Structure Theory > Ab Initio Electronic Structure Methods Software > Quantum Chemistry Data Science > Computer Algorithms and Programming Abstract : The QCArchive project of the Molecular Sciences Software Institute.